Cathelicidin-Derived Antimicrobial Peptides Inhibit Zika Virus Through Direct Inactivation and Interferon Pathway - He, Miao (Front Immunol, 2018)
Zika virus (ZIKV) is a neurotrophic flavivirus that is able to infect pregnant women and cause fetal brain abnormalities. Although there is a significant effort in identifying anti-ZIKV strategies, currently no vaccines or specific therapies are available to treat ZIKV infection. Antimicrobial peptides, which are potent host defense molecules in nearly all forms of life, have been found to be effective against several types of viruses such as HIV-1 and influenza A. However, they have not been tested in ZIKV infection. To determine whether antimicrobial peptides have anti-ZIKV effects, we used nine peptides mostly derived from human and bovine cathelicidins. Two peptides, GF-17 and BMAP-18, were found to have strong anti-ZIKV activities and little toxicity at 10 µM in an African green monkey kidney cell line. We further tested GF-17 and BMAP-18 in human fetal astrocytes, a known susceptible cell type for ZIKV, and found that GF-17 and BMAP-18 effectively inhibited ZIKV regardless of whether peptides were added before or after ZIKV infection. Interestingly, inhibition of type-I interferon signaling resulted in higher levels of ZIKV infection as measured by viral RNA production and partially reversed GF-17-mediated viral inhibition. More importantly, pretreatment with GF-17 and BMAP-18 did not affect viral attachment but reduced viral RNA early in the infection course. Direct incubation with GF-17 for 1 to 4 h specifically reduced the number of infectious Zika virions in the inoculum. In conclusion, these findings suggest that cathelicidin-derived antimicrobial peptides inhibit ZIKV through direct inactivation of the virus and via the interferon pathway. Strategies that harness antimicrobial peptides might be useful in halting ZIKV infection.